The effect of exercise on cytokine concentration in equine autologous conditioned serum. (19th June 2022) - Hale, Josephine N.; Hughes, Kristopher J.; Hall, Sarah; Labens, Raphael
Abstract: Background: Autologous conditioned serum (ACS) is a commonly administered intra‐articular treatment for the management of osteoarthritis in athletic horses. Objectives: To investigate the influence of exercise on the concentration of cytokines in a non‐commercial method of ACS production. Study design: Non‐randomised cross over design. Methods: Whole blood was obtained from eight healthy Standardbred horses immediately prior to, 1 h and 24 h following a single bout of exhaustive exercise. Blood was processed using a non‐commercial method of ACS production. Fluorescent microsphere immunoassay (FMIA) analysis was performed to quantify Interleukin 1 receptor antagonist (IL‐1Ra), Interleukin‐10 (IL‐10), Interleukin 1β (IL‐1β) and tumour necrosis factor α (TNF‐α) concentrations at each time point. Mixed effect repeated measures analysis of variance (ANOVA) was used to compare the pre‐exercise and post‐exercise cytokine concentrations. Significance was set at P < 0.05. Results: A reduced concentration of IL‐1Ra (median 584.4, IQR 81.9–5098 pg/ml, p  = 0.004) and an increased concentration of TNF‐α (11.92, 9.28–39.75 pg/ml, P  = .05) at 1 h post‐exercise were observed when compared with baseline values (IL‐Ra 7349, 1272–10 760 pg/ml; TNF TNF‐α 11.16, 8.36–32.74 pg/ml). No difference in cytokine concentrations of IL‐10 or IL‐1β were found between any of the time points. Main limitations: The large biological variability and small sample size represents limitations of this study. Conclusions: These results suggest that a single bout of intense exercise can reduce the concentration of the anti‐inflammatory cytokine IL‐1Ra and increase the concentration of the pro‐inflammatory cytokine TNF‐α, reducing the 'anti‐inflammatory' cytokine composition of ACS. Our findings suggest that collection of blood for ACS production should be performed no sooner than 24 h following a single episode of intense exercise. Résumé: Introduction/Contexte: Le sérum autologue conditionné (ACS) est fréquemment administré de façon intra‐articulaire dans les cas d'ostéoarthrose chez l'athlète équin. Objectifs: Tait d'Investiguer l'influence de l'exercice sur la concentration des cytokines dans l'ACS produit de façon non‐commerciale. Type d'étude: Étude croisée non‐aléatoire. Méthodes: Le sang entier de 8 chevaux Standardbred en santé a été prélevé immédiatement, 1 heure et 24 heures suivant un seul épisode d'exercice intense. Le sang a été traité en utilisant une méthode de production d'ACS non‐commercialisée. Une analyse par test immunologique à microsphères (FMIA, fluorescent microsphere immunoassay) a été effectuée afin de quantifier la concentration dans le temps du récepteur antagoniste de l'interleukine 1 (IL‐1Ra), interleukine 10 (IL‐10), interleukine 1 beta (IL‐1β) et du facteur de nécrose tumorale alpha (TNF‐α). Une analyse de variance ajustée par mesures répétées à effets mixtes a été utilisée pour comparer les concentrations de cytokines avant et après l'exercice. Les données avec une valeur de p  < 0.05 ont été considérées significatives. Résultats: Une concentration diminuée d'IL‐1Ra (médiane 584.4, IIQ 81.9–5098 pg/ml, p  = 0.004) et une concentration augmentée de TNF‐α (11.92, 9.28–39.75 pg/ml, p  = 0.05) ont été observées 1 heure après l'exercice par rapport aux valeurs de base (IL‐1Ra 7349, 1272–10760 pg/ml; TNF‐α 11.16, 8.36–32.74 pg/ml). Aucune différence de concentration de cytokines dans le temps n'a été identifiée pour IL‐10 et IL‐1β. Limites principales: Grande variabilité biologique et petite taille d'échantillon. Conclusions: Ces résultats suggère qu'une seule séance d'exercice intense puisse réduire la concentration de la cytokine anti‐inflammatoire IL‐1Ra et augmenter la concentration de la cytokine pro‐inflammatoire TNF‐α, ce qui réduirait la composition en cytokines anti‐inflammatoires dans l'ACS. Nos trouvailles suggèrent que le prélèvement de sang pour la production d'ACS devrait être fait au moins 24 heures suivant une période d'exercice.